The efficacy of a supervised and a home-based core strengthening programme in adults with poor core stability: a three-arm randomised controlled trial. Issue 6 (10th November 2014) - Chuter, V H; de Jonge, X A K Janse; Thompson, B M; Callister, R
Abstract : Background: Poor core stability is linked to a range of musculoskeletal pathologies and core-strengthening programmes are widely used as treatment. Treatment outcomes, however, are highly variable, which may be related to the method of delivery of core strengthening programmes. We investigated the effect of identical 8 week core strengthening programmes delivered as either supervised or home-based on measures of core stability. Methods: Participants with poor core stability were randomised into three groups: supervised (n=26), home-based (n=26) or control (n=26). Primary outcomes were the Sahrmann test and the Star Excursion Balance Test (SEBT) for dynamic core stability and three endurance tests (side-bridge, flexor and Sorensen) for static core stability. The exercise programme was devised and supervised by an exercise physiologist. Results: Analysis of covariance on the change from baseline over the 8 weeks showed that the supervised group performed significantly better on all core stability measures than both the home-based and control group. The home-based group produced significant improvements compared to the control group in all static core stability tests, but not in most of the dynamic core stability tests (Sahrmann test and two out of three directions of the SEBT). Conclusions: Our results support the use of a supervised core-strengthening programme over a home-based programme to maximise improvements in core stability, especially in its dynamic aspects. Based on our findings in healthy individuals with low core stability, further research is recommended on potential therapeutic benefits of supervised core-strengthening programmes for pathologies associated with low core stability. Trial registration number: ACTRN12613000233729.